Penile strangulation with a plastic bottle neck: Intervened by an atypical instrument: A case report. (August 2021) - Neupane, Durga; Singh, Sudhir Kumar; Kafle, Awaj; Chaudhary, Samir; Subedi, Sushil Sharma; Chhetri, Sunit
Abstract: Introduction and importance: Strangulation of penis, a surgical emergency, is often encountered in patients with psychiatric disorders and patients attempting to increase sexual arousal. Materials ranging from metallic to non-metallic like plastic bottles are used by the patients. The important factors to be considered for the successful treatment include the availability of instruments and the surgical skills of the doctor. Case presentation: A 45 year-old man with a comorbidity of severe depression presented to Emergency with a two months long history of penile strangulation with a plastic bottle neck. The gross appearance of the penis showed edema and proliferative growths. He was intervened with a cable wire cutter as standard instrument failed to do so. The patient was discharged on the same day of intervention. However, he was lost to subsequent follow up. Discussion: Penile strangulation which is common in people with mental disorders should be considered as a surgical emergency as it can present with devastating complications. No specific methods and tools have been recommended for the removal of those objects. The shame felt by patient is the root cause for late surgical consultation and are prone to develop complications. Simple instruments can be used for the intervention provided good surgical skills are demonstrated. Conclusion: Common in psychiatric patients who deny medical attention due to shame, penile strangulation should be intervened quickly and simple instruments not routinely used in surgical practice can be effectively used to remove the offending objects. Highlights: Penile strangulation is a surgical emergency. Offending objects can be metallic or non-metallic. Usually noted in psychiatric patients to augment sexual desire. Management is non-specific. A simple wire cutter can be used to cut the plastic bottle neck.